Students’ perception of environmental quality in public Secondary schools of Ibadan Metropolis, Nigeria - Mobolaji, David; Durotoye, Ayomikun; Daramola, Oluwole (Видавництво Львівської політехніки, 2024)
The study examined students’ perception of environmental quality in public secondary schools of Ibadan Metropolis, Nigeria. Multistage sampling procedure was employed for the study. The three categories of public secondary schools (all-boys and all-girls and co-educational) were identified with one school in each category randomly selected. Through this method, 128, 108 and 105 students in the all-boys and all-girls and co-educational schools respectively were selected for questionnaire administration making a total of 341 respondents. Findings revealed that variation exists in the socio-demographic characteristics of the students whereas the variation was more pronounced in all-boys school when compared with other schools. Across the study area, there were inadequate environmental amenities, although the condition of the available ones was bad especially in all-boys and co-educational schools. The study recommended the need for government to provide adequate environmental amenities through public-private partnership thereby enhance good quality of public secondary schools.
Keywords: environmental quality; Ibadan Metropolis; perception; public Secondary schools; students